Gene-agnostic therapeutic approaches for inherited retinal degenerations - John, Molly C.; Quinn, Joel; Hu, Monica L.; Cehajic-Kapetanovic, Jasmina; Xue, Kanmin (Frontiers in Molecular Neuroscience, 2023)
Inherited retinal diseases (IRDs) are associated with mutations in over 250 genes and represent a major cause of irreversible blindness worldwide. While gene augmentation or gene editing therapies could address the underlying genetic mutations in a small subset of patients, their utility remains limited by the great genetic heterogeneity of IRDs and the costs of developing individualized therapies. Gene-agnostic therapeutic approaches target common pathogenic pathways that drive retinal degeneration or provide functional rescue of vision independent of the genetic cause, thus offering potential clinical benefits to all IRD patients. Here, we review the key gene-agnostic approaches, including retinal cell reprogramming and replacement, neurotrophic support, immune modulation and optogenetics. The relative benefits and limitations of these strategies and the timing of clinical interventions are discussed.